Emotional Intelligence Concept, Paradigm and Implications - AhujA, Amit (JOURNAL OF INDIAN EDUCATION, 2017)
Emotional intelligence is an ability of a person to unite emotions into thought and is an integrated concept that links cognitive and affective domains. Emotional intelligence helps people to solve real world problems, manage stress and in decision-making, as emotions facilitate cognitive processes to adapt to different situations, thus play a crucial role in life, learning and lifelong learning. For professionals, emotional intelligence is a powerful predictor of job performance. Having self-regard, courage for reality testing, control on impulse and being happy are the identifying features of an emotionally intelligent personality. But valid instruments related to measurement and developmental aspects of emotional intelligence are not exclusively available. The ability and mixed models work out as theoretical paradigms to explain emotional intelligence. The ability model describes emotional intelligence as a kind of pure form of general mental ability, and mixed models visualise the synchronization between general mental ability and personality characteristics of an individual like his/her state of being well and extent of optimism. These models further emphasise upon the recognition of certain central components with respect to emotional intelligence. Regarding implications with respect to the learners, their exposure is a dynamic learning scenario, where they may show stability in their social relationships and persistence in odd situations may ease the situations. Schools can foster emotional literacy, as a component of the school curriculum, where students may be provided an environment where they learn to control and manage their emotions and hence develop empathy towards others.